Azimat, Obat, dan Legitimasi Kuasa: Kajian Parateks Naskah Islam Sulawesi Tenggara dan Jawa Barat - Abdullah Maulani (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2022)
This article examines Islamic manuscripts stored in several collections of the people of Southeast Sulawesi (Baubau) and West Java (Cirebon and Indramayu), which have been digitized by the EAP British Library and the Digital Repository of Endangered and Affected Manuscripts in Southeast Asia (DREAMSEA). The study was conducted based on a paratext approach which explains the elements outside the written text in the manuscript. Practically, Arabic script and language are widely used in religious texts to transmit knowledge and Islamic teachings. However, it is not widely revealed that Arabic script and language are also used as magical practices such as amulets, medicine, invulnerability, the knowledge of using weapons, and the like used in various conflicts, both with others and with the colonial side. On the other hand, this paper illustrates that Arabic script and language in the magical tradition became an inseparable part of efforts to legitimize rulers in the archipelago in the 19th century.